Influence of weight status on bone mineral content measured by DXA in children - Francisco Sánchez Ferrer; Ernesto Cortes Castell; Francisco Carratalá Marco; Mercedes Juste Ruiz; José Antonio Quesada Rico; Ana Pilar Nso Roca (BMC Pediatrics, 2021)
Abstract Introduction Childhood obesity is a public health problem with repercussions in later life. As tissue formation peaks in childhood we determined how weight status influences bone mineral content. Material and methods We studied 553 children aged 4–18 years over 10 years (46.8% girls). We measured age, weight, height and through bone densitometry (DXA), bone mineral content (BMC), bone mineral density (BMD), and waist, arm and hip circumferences. The patients were divided into groups using the body mass index z-score: underweight, normal weight, overweight, obese and very obese. Results BMC and BMD values were highest in the normal-weight and overweight groups. Logistic regression showed bone mineralization was inversely associated with waist circumference, the association being positive for weight and age. No differences were found according to sex. Discussion Studies of the relationship between weight and bone mineralization report contradictory results, often because of different study designs. Moreover, studies in children are either few or with small samples. Our findings in a large sample show the importance of weight status in bone mineralization given the risk of bone fractures or osteoporosis. Conclusions Weight status influenced bone mineralization. BMC and BMD decreased in children with a higher degree of obesity. Waist circumference correlated negatively with bone mineralization.